2007
DOI: 10.1371/journal.pone.0000553
|View full text |Cite
|
Sign up to set email alerts
|

Oct4 Targets Regulatory Nodes to Modulate Stem Cell Function

Abstract: Stem cells are characterized by two defining features, the ability to self-renew and to differentiate into highly specialized cell types. The POU homeodomain transcription factor Oct4 (Pou5f1) is an essential mediator of the embryonic stem cell state and has been implicated in lineage specific differentiation, adult stem cell identity, and cancer. Recent description of the regulatory networks which maintain ‘ES’ have highlighted a dual role for Oct4 in the transcriptional activation of genes required to mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 60 publications
9
58
0
2
Order By: Relevance
“…Gene expression of Oct4 has been associated with several cell cycle and apoptosis genes in ES and differentiated cells [56]. Because our data demonstrated that Oct4 was modulated by ethanol (Figs.…”
Section: Ethanol Modulation Of Oct4 Is Not Correlated To Overall Cellmentioning
confidence: 52%
See 1 more Smart Citation
“…Gene expression of Oct4 has been associated with several cell cycle and apoptosis genes in ES and differentiated cells [56]. Because our data demonstrated that Oct4 was modulated by ethanol (Figs.…”
Section: Ethanol Modulation Of Oct4 Is Not Correlated To Overall Cellmentioning
confidence: 52%
“…As cells with low Nanog expression lose their pluripotency earlier than cells with higher Nanog levels [69], the expression pattern of Sox2, Oct4, and Nanog in S8 cells suggests that ethanol-exposed cells were differentiated beyond the Nanog gatekeeper barrier. Oct4 regulates several genes related to cell cycle and apoptosis, and downregulation of Oct4 during differentiation correlates positively with transcription of apoptotic genes and lineage commitment [56]. In our system, a twofold variation in the Oct4 protein level between differentiated cells exposed to ethanol and control cells did not translate into differences in the overall cell proliferation rate, cell cycle phase distribution, or apoptotic cells (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…3 It was later shown that oocytes can also be employed for the cloning of mammals. 4,5 However, the efficiency of mammalian cloning, as measured by the production of live-birth clones, is low and it has been suggested that this is due to the incomplete reprogramming of the somatic nucleus. 6 Embryonic stem cells (ESCs), like oocytes, contain reprogramming activity, and can be employed to reprogram somatic genomes through fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Oct-4, a Pou domain-containing transcription factor, has become a proxy for stemness in many different studies of adult stem cells and is an essential mediator of the embryonic stem cell state (Campbell et al 2007;Lengner et al 2008). Oct-4 expression has been demonstrated at different locations in the human body like bone marrow, hair follicles, breast, liver, or neural stem cell (Gupta and Rosenberg 2008;Jiang et al 2002;Reyes et al 2002;Yu et al 2006) and now also in nasal polyp cells.…”
Section: Discussionmentioning
confidence: 99%